Verse Form and Meaning in the Poetry of Vladimir Maiakovskii - Aizlewood, Robin (Modern Humanities Research Association, 2024)
Maiakovskii himself said that a rhythmical 'rumble' was the basis of his verse, and demonstrated the actual generation of his verse from the bare rhythmical gul through intermediate versions to its final verbal form. In this study Aizlewood examines the role played by meter in Maiakovskii's first major work Vladimir Maiakovskii. Tragediaa, and in five main love poems. These works can be interpreted as a composite whole, a single text in effect: the Tragedy serves as an introduction to an exploration in five parts of the theme of love. This book, originally published in paperback in 1989 under the ISBN 978-0-947623-22-7, was made Open Access in 2024 as part of the MHRA Revivals programme.